The “Network Society” moves in mysterious ways: 25 years in the reception of a core concept - Cardoso, C.; Costa, C. M.; Damásio, B.; Mendonça, S. (Quantitative Science Studies, 2025)
The “Network Society” is an analytical concept developed by Manuel Castells to describe a new form of societal organization underpinned by microelectronics and based on information flows. Since it was introduced in the 1990s, this key contribution to social theory has framed much of academic research and policy-relevant worldviews when it comes to understanding contemporary digital ways. By quantitatively exploring the impact of his contributions, this study inquires into how Castells' concept was received by scientific communities publishing in peer-reviewed academic journals. Through a comprehensive and integrative bibliometric analysis, the findings reveal a three-phase build-up process of appropriation and highlight how the concept was predominantly exploited in the domains of Communication and Sociology, with an emphasis on connectivity and its implications for governance and policymaking, particularly in Western countries. There is evidence of its adaptability in capturing the evolving opportunities and challenges of the digital era.